A versatile and robust analytical method for hyaluronan quantification in crosslinked products and complex matrices. (May 2021) - Soato, Matteo; Galesso, Devis; Beninatto, Riccardo; Bettella, Fabio; Guarise, Cristian; Pavan, Mauro
Abstract: Hyaluronic acid (HA), a naturally occurring biopolymer composed of repeating units of d -glucuronic acid and N-acetyl-glucosamine, is widely used as principal component of drugs, medical devices, nutraceuticals and cosmetics. Chemical modifications of HA or the presence of unmodified HA in complex matrices often brings common analytical techniques to fail its identification or quantification. In this work, a specific method for the quantification of HA and HA derivatives was developed and tested. After strong acid hydrolysis, polysaccharide depolymerization and N-acetylglucosamine deacetylation, quantitatively yielded glucosamine residues were derivatized using Fluorenylmethyloxycarbonyl chloride (FMOC), separated and quantitated by means of HPLC equipped with UV detection. The method was partially validated according to ICH Q2(R1) and successfully applied on different viscosupplements composed by modified HA or medical devices containing unmodified HA in complex matrices. Graphical abstract: Image 1 Highlights: Hyaluronic acid (HA) quantification is harsh in derivatives or in complex matrices. Glucosamine residue from HA acid hydrolysis can be detected by HPLC. Glucosamine detection in HA derivative and medical devices was validated. Such method could be applied to complex and biological matrices.